Adventures of Clinical Psychology - Michele Roccella (MDPI AG, 2021)
Clinical psychology strives to fully grasp the person in his totality and in his individuality, helping him adequately address his own deep internal suffering and discomfort, social uneasiness, and harmonize his own needs, desires and, attachments [...]